PERANCANGAN MANAJEMEN USER PADA HOTSPOT MENGGUNAKAN RADIUSDESK - Budiman, Muhammad; Suharyanto, Cosmas Eko (Computer Science and Industrial Engineering, 2022)
Hotspot network technology is currently very developed so that it allows the process of managing users on wireless network services. The system manager can manage bandwidth, usage, online duration, concurrent, remaining quota and several other features. AAA (administration, Accounting, Authentication) technology works in a timely manner, after testing this technology, it was found that there were obstacles when managing on a much larger scale. The author uses Radiusdek to solve this problem and is used as a radius server to manage users. The function of user management is to classify users and groups according to their hierarchy. Hotspot network at PT. Batam Bintan Telecommunications is currently still not developed and currently the hotspot network has only been applied to internal offices, because PT Batam Bintan Telekomunikasi is currently still focused on corporate customers and residential customers. It is a pity if it is not developed, especially since PT Batam Bintan Telekomunikasi is located in Batamindo Industrial park, which can make the dormitory area and the area around Batamindo a target for large-scale internet sales. Therefore, the author designed this system to build a hotspot network that can be used by dormitory users and visitors who aim to find work while in Batamindo Industrial park. In this system, users can independently register and select the desired service package without having to contact the admin first